Propuesta y validación del plan de uso de suelos en el marco de ordenamiento territorial del distrito de Soritor - López Tuesta, César Augusto (2012)
The present thesis, "'Proposal and validation ofthe plan use land in the frame ofTerritorial Classification of Soritor district ", is geared to contribute, as an information tool and territorial management that will allow for an adequate use of the soil resource, this information will allow local authorities and population adopt policies that enable better plan their activities in the territory, knowing its potential and limitations. The report is based on an evaluation generated from studies that have been carried out in Soritor district of, Moyobamba province of and San Martín department, Complemented and updated with information of georeferenced field obtained during the months of January 2009 to August 201 O, through socialization workshops, strategic planning of the territory and interviews. The applied methodology was elaborated on the basis of a previous diagnosis of place, taking as a principal strategy the involvement of the main authorities and society in general by promoting a working democratic, participatory, gender equity and social inclusion in all stages of the project. The results are in an analysis of the cartographic cuts and synthesis of the ecological and economic units ofthe Soritor district, on the basis ofthematic reports ofphysiography, soils, ability to use more land, geology, geomorphology, forestry, current use and proposals of conservation areas, in addition to submitting a land use plan and territorial policies that will assist the monitoring and supervision ofthe present study. It should be noted that the study has given priority to the analysis of LANDSAT satellite images TMS (2008) and LANDSAT TM7 (2009), the same that were processed using the Systems of Remote Sensing and Geographic Information Systems, using the Software ERDAS IMAGINE, ARCIINFO and ARC GIS, in addition to the extension file compatible DBF to Foxpro. This thesis shows how dynamically, participatory, has managed to make a proposal for a plan of land use and design of territorial policies, which will be a guidance document to implement spatial planning processes and thus contribute to the process of land use and environmental management that is being carried in Soritor district.